Effect of resistive-endurance exercises on myocardial tissue creatine kinase isoenzyme, IL-6 and IL-10 serum changes in male cardiovascular patients - Alireza Zamanı; Bijan Rajaeıan; Saeid Rostamı (Türk Spor ve Egzersiz Dergisi, 2015)
The aim of the present study was to investigate the effects of endurance-resistance (concurrent) training on changes of CKmb, interleukin-6, and IL-10 levels of heart disease in men. For this purpose, 38 patients referred to medical centers Cardiovascular Shahin Shahr city, were selected. The patients were underwent bypass surgery or angioplasty balloon. After, patients filled demographic questionnaire and tests were performed to determine risk factors. Also echocardiography (Simpson) and limited exercise test method (Noughton) were used to determine functional capacity and ejection fraction. Before and after the exercise, anthropometric measurements (weight, waist circumference, hip circumference and subcutaneous fat three regions), blood tests for IL-6, IL-10, CKmb and walk test for 6 min (for determining the physical capacity) were measured. The exercises were performed 3 days a week for 24 sessions, each session was one hour. Results showed that rehabilitation programs reduce CKmb and inflammatory cytokines. Totally, the present study showed rehabilitation program having resistance- endurance (concurrent) training can be appropriate in order to perform functional capacity in patients. This method of training can cause improvement in muscular power, VO2max and better cardiovascular performance and at last induce quality of life of patients.